1993
DOI: 10.1007/bf00146267
|View full text |Cite
|
Sign up to set email alerts
|

Relations of cardiovascular risk factors to aortic pulse wave velocity in asymptomatic middle-aged women

Abstract: Cross-sectional associations between aortic elasticity assessed by carotid to femoral pulse wave velocity (PWV) and cardiovascular risk factors were examined in 429 apparently healthy middle-aged women. PWV was strongly and positively related to blood pressure and hypertension. Weak but significant positive associations were also found between PWV and age, heart rate, some lipids and lipoproteins, blood glucose (either as a continuous or dichotomous variable), body mass index, haematocrit, leucocyte count and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
63
3
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 35 publications
13
63
3
3
Order By: Relevance
“…Our findings that traditional risk factors were associated with all 3 measures of subclinical cardiovascular disease are consistent with our previous findings in women with SLE and the findings of other studies in nonlupus populations (36)(37)(38)(39)(40)(41). These factors include older age, high blood pressure, high cholesterol, smoking, and elevated glucose and insulin levels.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that traditional risk factors were associated with all 3 measures of subclinical cardiovascular disease are consistent with our previous findings in women with SLE and the findings of other studies in nonlupus populations (36)(37)(38)(39)(40)(41). These factors include older age, high blood pressure, high cholesterol, smoking, and elevated glucose and insulin levels.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have also shown that arterial stiffness measured by carotid-femoral PWV reflects the sclerotic rather than atherotic component of atherosclerosis. 21,36) These findings suggest that the influence of lipid parameters on PWV is weak.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, three different groups found no significant correlation between smoking status and increased cfPWV. [41][42][43] However, AIx was increased in smokers (17.25%) compared with nonsmokers (11.75%; P¼0.004) in one of the same subject Smoking and arterial stiffness RJ Doonan et al Smoking and arterial stiffness RJ Doonan et al populations. 42 A number of other studies found AIx to be increased in chronic smokers compared with nonsmokers.…”
Section: Chronic Smokingmentioning
confidence: 97%